Microfluidic Preparation of 89Zr-Radiolabelled Proteins by Flow Photochemistry - Daniel F. Earley; Amaury Guillou; Dion van der Born; Alex J. Poot; Jason P. Holland (Molecules, 2021)
89Zr-radiolabelled proteins functionalised with desferrioxamine B are a cornerstone of diagnostic positron emission tomography. In the clinical setting, 89Zr-labelled proteins are produced manually. Here, we explore the potential of using a microfluidic photochemical flow reactor to prepare 89Zr-radiolabelled proteins. The light-induced functionalisation and 89Zr-radiolabelling of human serum albumin ([89Zr]ZrDFO-PEG3-Et-azepin-HSA) was achieved by flow photochemistry with a decay-corrected radiochemical yield (RCY) of 31.2 ± 1.3% (n = 3) and radiochemical purity >90%. In comparison, a manual batch photoreactor synthesis produced the same radiotracer in a decay-corrected RCY of 59.6 ± 3.6% (n = 3) with an equivalent RCP > 90%. The results indicate that photoradiolabelling in flow is a feasible platform for the automated production of protein-based 89Zr-radiotracers, but further refinement of the apparatus and optimisation of the method are required before the flow process is competitive with manual reactions.